NILAI-NILAI KARAKTER DALAM TRADISI KIRAB BUDAYA PANGERAN ANGKAWIJAYA PADA MASYARAKAT DESA LOSARI LOR KECAMATAN LOSARI KABUPATEN BREBES (Civic Education Program, Universitas Negeri Semarang, 2022)
Kirab Budaya Pangeran Angkawijaya is a tradition that is carried out to honor the services of Pangeran Angkawijayawho has spread Islam in the Losari area. This tradition is carried out every year in Losari Lor Village, Losari district, Brebes Regency. The tradition of preserving this research uses a qualitative approach. The source of research data is primary data in the form of interviews, while secondary data in the form of dokumentation. The data collection technique used is interview observation and dokumentation of the validity of the data using triangulation of data sources. The data analysis used is an interactive method with the stages of data collection, data reduction, data presentation and conclusing drawing. The results showed that the hallmark of Kirab Pangeran Angkawijaya was displaying various kinds of works by Pangeran Angkawijaya including the Paksi Naga Liman chariot, Singa Barong Carriage, mask dance performance, Jaipong dance, Pencak Silat, Debus, and the heirlooms of Pangeran Angkawijaya. Character values in the tradition Kirab Budaya Pangeran Angkawijaya include religious mutual assistance, care for the environment, social care, tolerance and creativity. The meaning of this tradition is among onthers, a form a community gratitude of Allah SWT, respcet for Pangeran Angkawijaya who has contibuted to spreading Islam in the Losari area, uniting the Losari Lor Village community and its surroundings and preservation of culture in the Losari sub-district and its surroundings is an effort to preserve this tradition, namely with the role of the village government, the role of the community in introducing through social media and building awareness to all elements to maintain the tradition.Suggestions, research on this tradition should be developed again in terms of function, public perception, moral values, because this tradition needs to be preserved as local wisdom of local culture, especially in Brebes district.